Evaluasi Efektivitas Program Pendidikan Karakter dalam Pembentukan Nilai Positif di SMA Negeri 16 Konawe Selatan - Nur Atia; Syamsu A Kamaruddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to evaluate the effectiveness of the character education program in shaping students’ positive values at SMA Negeri 16 Konawe Selatan, in accordance with the research problem, which focuses on assessing the level of program achievement and identifying key factors that support its success. A quantitative approach was employed using a survey method involving 100 students from grade XI selected through proportional random sampling. The research instrument consisted of a Likert-scale questionnaire covering four main indicators: discipline, responsibility, honesty, and social concern. Data were analyzed using descriptive statistics to determine the effectiveness of the program and simple regression analysis to examine the influence of program implementation on the development of students’ positive values. The results indicate that the character education program is categorized as effective, with an average achievement score of 82.3%. Regression analysis revealed a significant influence between program implementation and the formation of positive student values (R² = 0.67; p < 0.05). These findings show that teacher role modeling, consistent implementation of activities, and a supportive school environment play crucial roles in strengthening the internalization of character values. The discussion further highlights that the success of the program is driven by the involvement of the entire school community, along with continuous habituation activities. Therefore, this study concludes that the character education program at SMA Negeri 16 Konawe Selatan has been effectively implemented and has contributed positively to students’ behavior. However, improvements are still needed in the areas of personalized guidance and collaboration with parents to optimize its outcomes. Keywords: character education, positive values, program effectiveness, school evaluation